Immobilization of Cadmium (CD) in Soil from the Talang Gulo Landfill Using Palm Shell Biochar - Nuranjani, Nuranjani; Damris, Damris; Saad, Asmadi (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Cadmium (Cd) levels in well water near the Talang Gulo Landfill (TPA) reached 0.064 mg/L, approximately 19 times higher than the clean water quality standards set by the Minister of Health Regulation No. 02 of 2023. Cd concentrations decreased with increasing distance from the landfill, indicating the mobilization of Cd from the landfill soil into the surrounding environment. Given the toxic and highly mobile nature of Cd, mitigation efforts are needed to suppress the movement of this heavy metal. Objective: This study aims to evaluate the effectiveness of palm oil shell biochar in immobilizing cadmium (Cd) in landfill soil through changes in solubility under water extraction and simulated acidic conditions. Methods: This study used a laboratory experimental method with the addition of palm oil shell biochar to the Talang Gulo landfill soil at doses of 0%, 5%, and 10% and an incubation time of up to 60 days. Results and Discussion: The addition of biochar can increase soil pH and significantly reduce Cd mobility, with immobilization efficiency increasing with increasing biochar dose and incubation period. Conclusion: Palm oil shell biochar has the potential to be used as an environmentally friendly ameliorant solution for the remediation of cadmium-contaminated soil